Contributions to Nephrology 2004
DOI: 10.1159/000082541
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemic Syndromes in Cancer Patients

Abstract: Early recognition of metabolic abnormalities in cancer patients at risk for hyperuricemia is essential for proper therapy. Prospective studies to assess the incidence of and risk factors for hyperuricemic syndromes in patients treated with uricolytic agents are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 75 publications
(102 reference statements)
0
19
0
Order By: Relevance
“…The best known example of crystal-induced tubulopathy is tumor lysis syndrome in which the pathogenesis of AKI is thought to be mediated by the precipitation of uric acid into crystals that obstruct the distal tubules and collecting ducts of the kidney [20], [21], [22]. Typically this occurs when a subject with a large tumor burden is treated with chemotherapy, especially in subjects where the tumor is extremely sensitive to such therapy such as after cytoreductive therapy for leukemia or lymphoma [23].…”
Section: Uric Acid In Acute Kidney Injurymentioning
confidence: 99%
“…The best known example of crystal-induced tubulopathy is tumor lysis syndrome in which the pathogenesis of AKI is thought to be mediated by the precipitation of uric acid into crystals that obstruct the distal tubules and collecting ducts of the kidney [20], [21], [22]. Typically this occurs when a subject with a large tumor burden is treated with chemotherapy, especially in subjects where the tumor is extremely sensitive to such therapy such as after cytoreductive therapy for leukemia or lymphoma [23].…”
Section: Uric Acid In Acute Kidney Injurymentioning
confidence: 99%
“…XOR plays a prominent role in both cancer types as the source of UA, and current therapies are directed at inhibition of XOR with allopurinol or Febuxostat and degradation of the SUA using recombinant uricase (Rasburicase). Recent reviews provide excellent discussion of both cancer states and therapeutic strategies for reducing the associated hyperuricemia [141,142]. …”
Section: Reviewmentioning
confidence: 99%
“…Univariate analysis revealed that hyperuricemia was associated with azotemia, hypercreatinemia, high LDH, and high white blood cell counts (the latter only in patients with leukemia), which is almost in accordance with previous reports. [2,4,7] We encountered two patients with clinical TLS in this investigation. Our definition for clinical TLS is having two or more metabolic disorders of hyperuricemia, hypercreatinemia, azotemia, and hyponatremia with oliguria.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Hyperuricemia usually occurs after the initiation of cancer chemotherapy, although it sometimes occurs spontaneously without any treatment. Tumor lysis syndrome (TLS) is a severe and deleterious form of several metabolic disorders, including hyperuricemia, hyperkalemia, hyperphosphatemia, and azotemia.…”
Section: Introductionmentioning
confidence: 99%